2014
DOI: 10.1111/brv.12109
|View full text |Cite
|
Sign up to set email alerts
|

The eunuch phenomenon: adaptive evolution of genital emasculation in sexually dimorphic spiders

Abstract: Under natural and sexual selection traits often evolve that secure paternity or maternity through self-sacrifice to predators, rivals, offspring, or partners. Emasculation-males removing their genitals-is an unusual example of such behaviours. Known only in insects and spiders, the phenomenon's adaptiveness is difficult to explain, yet its repeated origins and association with sexual size dimorphism (SSD) and sexual cannibalism suggest an adaptive significance. In spiders, emasculation of paired male sperm-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 96 publications
(332 reference statements)
0
30
0
Order By: Relevance
“…We scored araneoid spider shape dimorphism from the taxonomic literature as a simple presence/absence character (Table S2), and obtained SSD indices from recent SSD studies (Cheng and Kuntner 2014;Kuntner et al 2015). We followed a recent study of emasculation evolution (Kuntner et al 2015) in devising a genus level phylogeny from Dimitrov et al (Dimitrov et al 2012), but we modified the familial relationships according to the newest phylogenomic topology (Bond et al 2014).…”
Section: Genus Level Analyses: Araneoideamentioning
confidence: 99%
“…We scored araneoid spider shape dimorphism from the taxonomic literature as a simple presence/absence character (Table S2), and obtained SSD indices from recent SSD studies (Cheng and Kuntner 2014;Kuntner et al 2015). We followed a recent study of emasculation evolution (Kuntner et al 2015) in devising a genus level phylogeny from Dimitrov et al (Dimitrov et al 2012), but we modified the familial relationships according to the newest phylogenomic topology (Bond et al 2014).…”
Section: Genus Level Analyses: Araneoideamentioning
confidence: 99%
“…We define polygyny as male mating with more than one female, whereas monogynous males invest into repeated mating with the same female in an attempt to plug both of her copulatory openings. We based the inferred mating rates in nephilids and outgroups (Additional file 1: Table S1) on available experimental studies [13, 3941, 48–73] and on genital damage data where single versus multiple male mating plugs per female copulatory opening predict monandry and polyandry, respectively [26, 35, 40, 41, 53]. Most Nephila species, and Phonognatha graeffei, are polyandrous [49, 61].…”
Section: Methodsmentioning
confidence: 99%
“…Relatively small nephilid males of certain species engage in extreme mating strategies, including severing terminal parts of their pedipalps (sperm transferring appendages), which are used to plug female copulatory openings [39, 40]. Experimental studies on selected species found that plugs from males with complex genitals commonly prevent female polyandry, whereas plugs from simple genitals do not [39, 41].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, such breakages could be adaptive if they increase a male's reproductive success. For example, in many spider species a portion of the male copulatory organ frequently breaks off inside the female reproductive tract during mating, and can act as a mating plug, preventing subsequent males from being able to inseminate the female (Snow et al, 2006;Uhl et al, 2010;Kuntner et al, 2015). In some species essentially all matings result in breakage (Uhl et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In some species essentially all matings result in breakage (Uhl et al, 2010). Though breakage typically renders the copulatory organ nonfunctional, this strategy is likely favoured because males typically encounter few females and so have limited opportunities to mate (Uhl et al, 2010;Kuntner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%